A Preliminary Kinematic Gait Analysis of a Strongman Event: The Farmers Walk - Justin W. L. Keogh; Anthony Kattan; Scott Logan; James Bensley; Che Muller; Linda Powell (MDPI AG, 2014)
This study sought to obtain some preliminary sagittal plane kinematic data on a common strongman event (and conditioning exercise) 'the farmers walk' and gain some insight into its kinematic determinants. Five experienced resistance trained males performed three, 20 m farmers walks at maximal speed while carrying 90.5 kg in each hand. Farmers walk average velocity was significantly greater in the middle (8.5-11.5 m) and latter (17-20 m) than initial stage (0-3 m), with this also associated with significant increases in stride length and stride rate and reductions in ground contact time. Comparisons between each subject's fastest and slowest trials revealed virtually no significant differences. In contrast, the fastest three trials (irrespective of subject) had significantly greater stride length, stride rate and reduced ground contact time than the slowest three trials. Based on the impulse-momentum relationship, the production of high anterior-posterior and vertical impulses over short ground contact times may be crucial for farmers walk performance. Future studies should utilise larger samples and investigate the ground reaction and joint kinetics of the farmers walk and compare these values to other forms of bipedal gait and resistance training exercises to get a more complete understanding of the biomechanics of this exercise.